2022
DOI: 10.1021/acs.oprd.2c00088
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Liquid–Liquid Biphasic Flow Alkylation and Continuous Crystallization Using Taylor Vortex Flow Reactors

Abstract: This work established the integration of a continuous flow reaction and continuous crystallization using Taylor vortex flow reactors. We previously developed liquid–liquid biphasic flow alkylation using a Taylor vortex flow reactor, which is a scalable flow reactor with high mixing efficiency. To maximize the efficiency of this methodology, we evaluated process parameters and instrumental parameters, such as the rotating speed and tilt of the reactor, and optimized the reaction conditions. As a result, the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…After a thorough study of conditions to avoid clogging, a long run processing >100 g was achieved, giving the product in 95% yield and >99% purity [116]. The same authors also reported the crystallization of a simple dipeptide with the aim to overcome issues found in batch in relation to product stability and scale-up concerns.…”
Section: Inline Precipitation and Crystallizationmentioning
confidence: 99%
“…After a thorough study of conditions to avoid clogging, a long run processing >100 g was achieved, giving the product in 95% yield and >99% purity [116]. The same authors also reported the crystallization of a simple dipeptide with the aim to overcome issues found in batch in relation to product stability and scale-up concerns.…”
Section: Inline Precipitation and Crystallizationmentioning
confidence: 99%
“…In this context, we considered that a Taylor vortex flow reactor (TVFR) based on the PFR system could offer a possible solution. TVFR has a simple structure, with the rotation axis generating Taylor vortices at the narrow gap in millimeters between the outer cylinder and the rotation axis, which yields high shear stress and enhances mixing efficiency (Figure a) . The larger cross-sectional area compared with a standard tube reactor is advantageous for mitigating the risk of clogging.…”
Section: Introductionmentioning
confidence: 99%
“…35 A process for imine with reactive crystallization in a Taylor vortex flow reactor was achieved due to high mixing efficiency. 36 In recent years, TCR has also been applied to the photocatalytic degradation of pollutants due to its high photon utilization efficiency. However, the current research mainly focuses on the improvements of TCRs on photodegradation efficiency through experiments without dissecting the role of TCRs played in the advancement of HPCT.…”
Section: Introductionmentioning
confidence: 99%